Effects of dynamics and trigger on energy absorption of composite tubes during axial crushing. Issue 5 (3rd September 2021) - Chambe, J.-E.; Bouvet, C.; Dorival, O.; Rivallant, S.; Ferrero, J.-F.
Abstract: The purpose of this study is to complete a previous quasi-static experimental campaign on the energy absorption performance of composite tubes with the influence of the dynamic effect. Various hybrid composite tubes, involving unidirectional and braided plies with various materials and stacking sequences, were tested both in quasi-static and in dynamic crushing in order to identify their behavior and determine their absorbing capabilities using the Specific Energy Absorption. In dynamic loading, 90°-oriented fibers stabilised by woven plies showed good performances, contrary to static loading, since the energy absorption of the unidirectional laminate oriented at 0° drops by 50% in dynamics.